Self-Assessment of Writing in Learning English as a Foreign Language The Case Study of Second Year LMD Students of English at University of Laghouat - DOUIB ,NOURELHOUDA; BAADACHE ,FADHILA; BOUMEDIENE, HOUDA (Faculty of Letters and Foreign Languages Department of English, 2017)
The present study is an attempt made to investigate a possible way of using self-assessment method in English as a Foreign Language (EFL) writing classroom. The main objective of this study is to explore the role of self-assessment in developing students’ skills and abilities in their writing process. This research also explores how 50 second year students at the English Department- University of Laghouat perceived their own writing skills and whether this perception is affected by self-assessment practices. To achieve this model, Pre/Post test and questionnaire were administrated to the sample of the study. These tools were used to test EFL learners’ level and to measure what they have learnt from using self-assessment strategy. The work is divided into two parts: A theoretical part with two chapters about assessing writing and self-assessment strategy, and a practical part that involves the research design and interpretation of the results.The findings showed that learners lack the competence of evaluating their pieces of writing;however,it can be developed through applying selfassessment tool in writing classroom. Additionally, the present study emphasized the importance of building learners’ autonomy and interaction in their own learning process which aid them to be successful lifelong learners